Electrical resistivity tomography (ERT) applied in the detection of inorganic contaminants in suspended aquifer in Leme city (Brazil) - Moreira, Cesar Augusto [UNESP]; Carrara, Alan [UNESP]; Helene, Lívia Portes Innocenti [UNESP]; Hansen, Marco Antônio Fontoura; Malagutti Filho, Walter [UNESP]; Dourado, João Carlos [UNESP] (My University, 2017)
The assessment of contamination caused by improper disposal of solid waste involves integrated analysis of the physical environment, which shall range from the location of the pollutant source, flow paths and accumulation zones. The environmental diagnosis in complex aquifer systems shall clearly define the dimensions of the contaminated area by means of technical options that allow the adequate location of wells for quantification of contents. This work presents the results of the use of Electric Resistivity Tomography (ERT) in the mapping of leachate originated from the decomposition of organic matter contained in clandestinely buried residues. Eight parallel lines were carried out in addition to a reference line, in an area defined from a satellite image history. In the area occurs a geological unit composed of alternating centimetric layers of siltstones and argillites, with lenses of fine sandstone filled by carbonaceous cement, deposited in a shallow marine environment with influence of fluvial sedimentation. The analysis of the 2D inversion models based on the physicochemical characteristics of the leachate allowed the identification of individualized areas of electrical resistivity lower than the natural minimum for the area, which shall reflect zones of origin, flow and accumulation of leachate. 3D models and multilevel electrical resistivity maps generated from the inversion models allowed for the detailing of areas of low resistivity, which reveal areas of independent leachate accumulation, disconnected and at various depths, supported by a suspended aquifer system composed by levels of fine sandstone cemented.
Keywords: 3D modeling; Contamination; Electrical resistivity; Leachate; Suspended aquifer